(untitled) - Baglet, Desmond (Oxford, 1998)
Hurricane Mabel is going to be very nasty indeed. David Wyatt, ayoung weather scientist, has a strangefeeling about Mabel. She should stay out at sea and not come near the Caribbean island of San Fernandez. But Wyatt believes she will change direction and hit the island. He can't explain why - he just knows he is right. While Mabel moves slowly northwards, some people on San Fernandez are worrying about another danger - war, which also brings death. War seems more important to them. They can flight a war, and win. But they can't fight a hurricane, so they should listen to Wyatt... before it is too late.
Keywords: English fiction,English literature; 20th century